Management of immune checkpoint inhibitor-associated toxicities in older adults with cancer: recommendations from the International Society of Geriatric Oncology (SIOG) : policy review - Mac Eochagain, Colm; Neuendorff, Nina Rosa; Gente, Karolina; Leipe, Jan; Verhaert, Marthe; Sam, Christine; de Glas, Nienke; Kadambi, Sindhuja; Canin, Beverly; Gomes, Fabio; Decoster, Lore; Korc-Grodzicki, Beatriz; et al. (The lancet. Oncology, 2025)
Immune checkpoint inhibitors (ICIs) have substantially advanced the treatment landscape for a wide variety of malignancies. Older adults represent a large and rapidly growing demographic, among whom ICIs are widely prescribed. Management of ICI-associated toxicity among older adults, particularly in the presence of frailty and comorbidity, poses unique challenges. In this Policy Review, developed by the International Society of Geriatric Oncology (SIOG), we offer an evidence-based framework for health-care providers, caregivers, and policy makers for treating older adults with ICIs, focusing on unique considerations for this population that are not adequately addressed by existing guidelines, and expanding them to encompass geriatric oncology principles.